FREE TUTORIAL PROGRAM AND ITS EFFECTS TO MATHEMATICS PERFORMANCE OF COLLEGE STUDENTS AT PAMPANGA STATE AGRICULTURAL UNIVERSITY PHILIPINES - Jocell Calma; Aiza Villavicencio (Paedagogia: Jurnal Pendidikan, 2022)
The free tutorial program of the Mathematics Society members and Department of Mathematics faculty members is an extension activity implemented semesterly in preparation for both midterm and final examinations on selected Mathematics subjects at Pampanga State Agricultural University. Pre-test and post-test were administered to students who voluntarily participated before and after the free tutorial program. Using the inferential method of research, the results showed that the pre-test performance of students is significantly different to the post-test across all the free tutorial programs conducted from 2014 to 2018. Moreover, the tutorial performance and the major examination performance of students were significantly related. Thus, the free tutorial program is effective for students who participated in the tutorial program. The findings of the study suggest the continuation of the tutorial program with wider dissemination for the increase of participants.